Care to child with muscular dystrophies dependent of home technology: mothers´ conception - Fabíola Sousa de Oliveira; Viviane Mamede Vasconcelos; Mariana Cavalcante Martins; Ingrid Martins Leite Lúcio (Universidade Federal do Ceará, 2013)
It was aimed to understand the mother's conception on care to child with muscular dystrophies dependent on technology. Descriptive study with qualitative approach carried out in a children's hospital of the tertiary net in Fortaleza-Ceará, Brazil, as well as in homes of children with muscular dystrophy assisted by the Home Ventilation Assistance Program. The informants were mothers of children with dystrophy aged between zero and four years old, admitted in the Special Patients Unit and assisted by this program. We performed semi-structured interviews and after analysis, the following categories emerged: Care of children with muscular dystrophy and Feelings and expectations of mothers of children with muscular dystrophy. We identified that some mothers consider the child's daily life within the normal patterns, and others report difficulties, creating anxiety and fear of death. Thus, we verify the importance of nurses in the training of these mothers for directed care enabling to overcome stressful moments.